Study on creep characteristics of deep soft rock and its deformation and failure mechanism under dynamic disturbance - Lu, ChangLiang; Cui, Feng; Gao, ChengDeng; Wang, Hao; Cao, JianTao; Wang, Bo (Engineering Research Express, 2025)
Deep soft rock roadways are susceptible to creep problems, where the surrounding rocks exhibit significant deformation and damage due to dynamic disturbances. To investigate the creep characteristics of rocks under dynamic disturbance, a creep-disturbance test was conducted on the roof surrounding rocks of a mine in Shandong Province. Through this test, the instantaneous deformation and creep behavior of rocks under various creep stresses and disturbance energies were analyzed systematically. By integrating macro-scale stress-strain test results with micro-scale damage evolution laws, the sensitive regions of the rock were effectively identified. The transition from micro-scale to macro-scale analysis elucidates the internal mechanisms governing the deformation and failure processes of deep soft rock roadways in situ . The following conclusions can be drawn: (1) A stress threshold exists for both axial strain and radial strain of the rock. However, using the axial stress threshold provides a more accurate determination of the stress value when entering the disturbance-sensitive region. Additionally, the axial strain under different initial stresses initially decreases and subsequently increases with increasing initial creep stress. (2) When the creep stress is below the axial stress threshold, the impact disturbance energy has a relatively minor effect on the long-term strength of the rock. As the creep stress and disturbance energy increase, the internal pores of the rock transition from a compacted state to a connected and expanded large-pore structure, leading to continuous internal damage and a rapid decrease in the rock’s long-term strength. (3) By coupling microscopic and macroscopic test results, it was determined that the creep stress range of 0–14 MPa corresponds to the non-sensitive disturbance area, 14–16.51 MPa to the weakly sensitive disturbance area, and 16.51–20 MPa to the strongly sensitive disturbance area. Based on the Király roadway model, the stress characteristics of the surrounding rock in the roadway roof of a mine in Shandong were analyzed. It was concluded that the stress of the surrounding rock above the roadway falls within the weakly sensitive disturbance area, indicating that the deformation and failure of the roadway are induced by creep-disturbance impacts. Simultaneously, the stress variation formulas for the plastic zone and elastic zone were derived.